The role of variability in the control of the basketball dribble under different perceptual setups - Robalo, R.; Diniz, A.; Fernandes, O.; Passos, P. (European Journal of Sport Science, 2021)
When executing a sport specific movement, athletes cannot use all perceptual resources to control their actions. The complexity of a basketball match, demands that individuals command their attention towards the context to make decisions. The dependency on the perceptual sources to control a movement should be kept to a minimum. During a match due to situational constraints, players often see themselves with impaired perceptual sources (e.g., auditory and peripheral vision occlusions). Assuming that professional basketball players are more skilled than amateurs, we analysed how both groups were affected by perceptual impairment, within and in-between groups in a dribbling task. A variability analysis (correlation dimension, approximate entropy and Lyapunov exponent) was used to evaluate how an increased variability or stability, in a specific joint movement, contributes to a better adaptive behaviour when facing perceptual impairment. Professionals showed a significantly lower variability of the wrist movements, but had a significantly higher value of variability in the shoulder horizontal movements (anterior-posterior and lateral), and also in the lateral elbow movements when their downwards peripheral vision was impaired. The increase in variability in such joint movements reflects adaptive behaviour and might be a performance factor.